2022
DOI: 10.31235/osf.io/pgv2x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeat Spreaders and Election Delegitimization: A Comprehensive Dataset of Misinformation Tweets from the 2020 U.S. Election

Abstract: This paper introduces and presents a first analysis of a uniquely curated dataset of misinformation, disinformation, and rumors spreading on Twitter about the 2020 U.S. Election. Previous research on misinformation — an umbrella term for false and misleading content — has largely focused either on broad categories, using a finite set of keywords to cover a complex topic, or on a few, focused case studies, with increased precision but limited scope. Our approach, by comparison, leverages real-time reports colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…• Leveraging manually curated annotations (Kennedy et al 2022;Abilov et al 2021), we observed how the "Stop the Steal" rhetoric was by far the narrative mostly amplified by coordinated actors. Further, we uncovered and verified that the vast majority of users involved in such manipulation actions were supporting and promoting claims about voter fraud (Abilov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…• Leveraging manually curated annotations (Kennedy et al 2022;Abilov et al 2021), we observed how the "Stop the Steal" rhetoric was by far the narrative mostly amplified by coordinated actors. Further, we uncovered and verified that the vast majority of users involved in such manipulation actions were supporting and promoting claims about voter fraud (Abilov et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many are thus concerned that platforms may be undermining democratic processes: in the United States, 73% of adults had "little or no confidence in tech companies to prevent the misuse of their platforms to influence the 2020 election" (Green, 2020). Given the widespread concern, urgency, and ambiguity surrounding the topic, researchers have devoted increasing attention toward understanding how platforms contribute to news audiences during elections (Edelson et al, 2021;Hecht et al, 2017;Kennedy et al, 2022;Mustafaraj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that superspreaders of misinformation -users who consistently disseminate a disproportionately large amount of lowcredibility content -may be at the center of this problem [15,45,21,12,51,6].…”
Section: Introductionmentioning
confidence: 99%
“…Social bots also played a disproportionate role in spreading content from lowcredibility sources [44]. The Election Integrity Partnership (a consortium of academic and industry experts) reported that during the 2020 presidential election, a small group of "repeat spreaders" aggressively pushed false election claims across various social media platforms for political gain [21,12].…”
Section: Introductionmentioning
confidence: 99%